Islamic Microfinance as Social Finance in Indonesia: A Review - Aisyah As-Salafiyah; Dwi Ratna Kartikawati (Islamic Social Finance, 2022)
Islamic microfinance is one of the Islamic social and financial instruments in increasing the productivity of MSMEs, which helps the country's economic development by providing capital. This study aims to determine the development map and trends of published research on the theme of Islamic microfinance in Indonesia. Data analyzed from more than 54 research publications Scopus indexed. The export data is then processed and analyzed using the R Biblioshiny application program to find the bibliometric map of the development of Islamic Microfinance in Indonesia. The research results show that the number of publications on the development of Islamic microfinance research in Indonesia continues to increase, where the results of the co-occurrence network of this theme show that there are four varied characters. At the same time, the thematic map divides it into four quadrants: dropping or emerging themes, basic themes, highly developed and isolated themes, and motor themes. In addition, this study also analyzes the most popular trend maps from journals, authors, affiliations, countries of correspondence and most cited countries.